3 Functional and radiological outcomes following medial patellofemoral ligament (MPFL) reconstruction. (20th December 2017) - Akhtar, MA; Raut, P; Bonner, T; Hui, A
Abstract : Our aim was to study the functional and radiological outcomes following MPFL reconstruction. 108 patients undergoing MPFL reconstruction between January 2009 and July 2014 were identified. Demographic details, functional outcomes and complications were studied. A random cohort of 21 knees was selected to study pre-operative radiological findings with a magnetic resonance imaging (MRI) scan and pre and post op x-rays to study the Insall-salvati ratio and the position of the MPFL screw in relation to the schottle point. The mean age was 25 years for 56 female and 52 males. The mean KOOS score was 44 before and 77 following MPFL reconstruction with an improvement of 33 points. The mean IKDC score was 38 before and 69 following a MPFL reconstruction with an improvement of 31 points. 3 patients (2.8%) had further episodes of instability. The mean Pre-op Insall Salvati ratio was 1.3 and post op was 1.2. Patella alta was present in 55%. Patella height was corrected in 73%. The most common position of MPFL screw from the schottle point was anterior and distal in 53%, followed by posterior and distal in 37%, anterior and proximal, and posterior and proximal in 5% each. The mean distance of MPFL screw from the schottle point was 11.8 mm (range 1–23 mm). There was improvement in functional scores following MPFL reconstruction. The failure rate was 2.8%. Patella alta was present in 55% preoperatively and it was corrected in 73% of cases. We recommend our technique of MPFL reconstruction to improve functional outcomes and correct patella alta.